PELATIHAN KOMPETENSI LINTAS BUDAYA DAN KETAHANAN BAGI PASUKAN PENJAGA PERDAMAIAN PBB: SEBUAH USULAN - Raden Mas Jerry Indrawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2018)
Does culture pose significant threat to UN Peacekeeping Forces in their line of duty in conflict areas? Does it affect their role as peacekeepers in midst of conflicts? Peacekeeping is not an ordinary military assignment, like in war. Peacekeeping Operation requires certain skills, such as cross-culture competence and high cultural resilience. Hence, peacekeeping work must be understand as an activity that rely more on cooperation, integration from all related stakeholders, and coordination between UN Peacekeeping Mission with other parties, like civilians, government, police, humanitarian workers, mass media, etc. nowadays, the complexity of UN missions requires variation in their training methods. This paper will discuss several of training programs involving the entire component of peacekeeping forces, including their family, regarding to cross-cultural competence and cultural resilience.